(untitled) (Research, Society and Development, 2022)
Objective: To develop and validate a previously constructed instrument to assess communication and humanization with patients’ relatives and family physician relationships, during the medical report, in the context of the Intensive Care Unit. Methodology: This is methodological research, with a quantitative and qualitative approach, carried out in 2020 and 2021. After the instrument was developed, the Delphi Technique was used to validate the content with the participation of eight experts. Data collection took place through interviews and questionnaires. In the data analysis, the Content Validity Index was calculated with a minimum agreement rate of 0.70. Results: The items that composed the instrument in relation to the issuer were: aspect of the professional, compliance and identification of the family, behavior of the doctor according to the reactions of the family members due to the great emotional burden, optimization of the consultation time, the doctor’s behavior during the consultation; to the receiver were: in case of patients incapable of decision, before the family; to the message were: information directed to the legal representative, regarding the information passed, control over the posture; to the environment were: characteristics of the environment, confidentiality and privacy during the conversation. Conclusion: All items had a CVI greater than 0.70. The instrument is able to assess what it proposes and how promising its application is in communication actions and doctor-patient relationships.